PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI PENERAPAN PEMBELAJARAN BERBASIS MASALAH DI SMP NEGERI 4 MEDAN - Antonius Simbolon, Waminton Rajagukguk dan (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This study consists of a shaped quasi experimental class treated problem-based learning and classroom learning control treated normal. Data were analyzed by T test and ANOVA analysis of two paths. The results showed that that (1) the mathematical problem solving ability of students who received problem-based learning (PBM) is better than the students who received the usual learning. This is evident from the results of the analysis of statistical tests to Thitung = 10.029 bigger Ttabel is 2.75. (2) There is no interaction between the learning model and the ability of students to the early mathematics problem solving ability of students. (3) The increase in mathematical problem solving ability of students were given a problem-based learning with an average N-Gain of 0.7 is high. Key Word : MathematicalÂ Communication , Problem-Based Learning